Melatonin Improved Waterlogging Tolerance in Alfalfa (Medicago sativa) by Reprogramming Polyamine and Ethylene Metabolism - Zhang, Qiang; Liu, Xiaofei; Zhang, Zhifei; Liu, Ningfang; Li, Danzhu; Hu, Longxing (Frontiers in Plant Science, 2019)
Melatonin (MT), polyamines (PAs) and ethylene have been suggested to play key roles in plant growth and development in response to environmental abiotic stresses. However, the effect of melatonin on polyamine and ethylene metabolism under water-logging stress has rarely been elucidated. The main purpose of this study was to investigate the effect of melatonin pretreatment on water-logging stress in alfalfa. The experiment was arranged into four treatment groups (control with water pretreatment (CK-MT), control with melatonin pretreatment (CK+MT), water-logging pretreated with water (WL-MT) and water-logging pretreated with melatonin (WL+MT)) with three replications. Six week old alfalfa seedlings were pretreated with 100 µM melatonin and exposed to water-logging stress for 10 days. Plant growth rate, different physiological characteristics and gene expression level were measured. Results showed that water-logging induced melatonin accumulation, and melatonin pretreatment increased endogenous MT levels for the control and water-logged plants. Water-logging stress caused significant reduction in plant growth, chlorophyll content, photochemical efficiency (Fv/Fm) and net photosynthetic rate (Pn), while increased leaf electrolyte leakage (EL) and malondialdehyde (MDA) content. Pretreatment with melatonin alleviated the water-logging induced damages and reduction in plant growth, chlorophyll content, Fv/Fm and Pn. Water-logging stress significantly increased leaf polyamines (Put, Spd, Spm) and ethylene levels, and the increased PAs and ethylene levels are coupled with the higher metabolic enzymes and gene expressions. Whereas pretreatment with melatonin further increased Put, Spd and Spm levels, but decreased ethylene levels under water-logging, and those increased PAs levels or decreased ethylene levels are regulated by the metabolic enzymes and gene expressions. The results in this study provides more comprehensive insight into the physiological and molecular mechanisms of melatonin improved water-logging tolerance in alfalfa, and suggested that melatonin improved water-logging tolerance in alfalfa at least partially by reprogramming ethylene and PAs biosynthesis that attribute to the increased PAs and decreased ethylene levels, which leads to more enhanced membrane stability and photosynthesis, as well as less leaf senescence caused by ethylene.